A Prospective Comparative Study Of Conservative And Surgical Management Of Varicose Veins (Indian Journal of Applied-Basic Medical Sciences, 2022)
Introduction : Varicose Veins are Defined as “ Permanently Elongated, Dilated vein/veins with tortuous path causing pathological circulation”.Varicose veins can develop anywhere in the body but are most commonly seen in the lower limbs. A detailed knowledge of the mechanism of hemodynamic failure and the underlying anatomy is important in deciding treatment of the patient with chronic venous disease. Methodology : The aim of this study was to determine the correlation between different complications of varicose veins and Recurrence rate of Complications with the treatment undergone by the patient. Total 30 patients were randomly assigned to Conservative management (i.e. Limb End Elevation, Elastic Stockings Application & Intermittent Bed rest to avoid prolonged Standing) or Surgical management (i.e. Trendelenburg Operation with Great Saphenous Vein Stripping). Special focus was given to the follow-up visit of the patients who were asked to be present for review every week, till two months so as to be vigilant regarding the occurrence of complications.Results : Out of 30 patients, 15 were treated surgically while 15 were treated conservatively. Eleven (11) patients in total developed some complications in post treatment part. The commonest complication observed in post surgical patients was haematoma. Recurrence of Varicosity was seen in 4 patients who were previously managed conservatively. A single case of wound infection and ulcer formation were observed in each respectively. Out of the 11 patients who had developed some complications, 5 patients had undergone surgical management, while 6 patients had undergone conservative management.Conclusion : Surgical Intervention is better than conservative management in Varicose veins. The rate of complications / recurrence over a 2 months period was less in the surgical group than in the group managed by conservative therapy.
Keywords: Varicose veins; Conservative and Surgical Management; Complications; Recurrence